Introduction (Scottish Historical and Archaeological Internet Reports, 2009)
Recent work in North Berwick has identified deeply stratified well-preserved deposits relating to the medieval and post-medieval development of the town, along with elements of structures and surfaces. The scale of the work allowed deposits to be recorded throughout the core of the medieval town, within the harbour. And towards the nunnery to the west, giving a more complete view of the archaeology of the burgh was previously possible.